GETTING RESEARCH IN THE CONTEXT OF ICT COMPETENCIES OF TEACHERS - KUBRICKY, Jan (Trends in education, 2016)
The paper presents partial, preliminary analysis of ICT skills of teachers in the context of a wider set of research, information and communication technologies in the work of primary school teachers. Attention is paid to modern approaches operationalization of ICT skills to teachers in a practical framework for transnational model and ICT skills created by UNESCO. Our main goal is to create a basis for the design research claims that would allow the identification of the key segments of the intentions of teachers and related needs for effective application of ICT in their own teaching.
Keywords: ICT; teacher's competence; UNESCO; research